EXAMPLES OF UNUSUAL IONOSPHERIC OBSERVATIONS MADE BY THE DEMETER SATELLITE OVER SEISMIC REGIONS - Parrot M.; Berthelier J.J.; Lebreton J.P.; Sauvaud J.A.; Santolik O.; Blecki J. (My University, 2006)
The micro-satellite DEMETER was launched on June 29, 2004 in a polar and circular orbit with an altitude of ~710 km. It is a CNES mission controlled from Toulouse in France. The main objective of DEMETER is to search and characterize ionospheric perturbations that can be associated with the seismic activity in order to better understand the generation mechanism of such perturbations. Its scientific payload allows us to measure waves in a broad frequency range and also some important plasma parameters (ion composition, electron density and temperature, energetic particles). This paper is a preliminary report of unusual observations recorded by DEMETER over seismic regions prior to earthquakes. The main purpose of the project is to perform a statistical analysis with many events in order to determine the necessary conditions to observe such seismo-electromagnetic effects. It is too early to perform such statistics but data recorded during selected events and shown here are useful since they may point out sensitive parameters which must be particularly surveyed in the statistical analysis. © 2006 Elsevier Ltd. All rights reserved.
Keywords: DEMETER; IONOSPHERE; SEISMIC ACTIVITY